Effects of buffer layer and thickness of window-layer on performance of highly efficient polycrystalline cadmium sulfide (cds)/cadmium telluride (cdte) solar cells - Thanihaichelvan, M.; Ravirajan, P.; Mahanama, G.D.K.; Dissanayake, M.A.K.L.; Colegrove, E.; Dhere, R.; Sivananthan, S. (University of Jaffna, 2013)
In this work, the effects of buffer layer and thicknesses of the window layer on performance of CdS/CdTe solar cells were studied. The quality and performance of the buffer layer and active layers was studied as a function of CdS layer thickness using atomic force microscopy and current density – voltage measurements of the corresponding cells, respectively. Short-circuit current density is significantly enhanced by introducing a buffer layer between bottom electrode and CdS. It is also highly dependent on the thicknesses of the window layer and is optimized for a window layer thickness of 50 nm. The optimized devices showed external quantum efficiencies over 85 % at the maximum absorption wavelengths of cadmium telluride and yield short circuit current densities up to 24 mAcm-2 for air mass (AM) 1.5 conditions (100 mW cm-2 , 1 sun). The AM 1.5 open circuit voltage reaches 0.82 V and the fill factor 0.73, resulting in an overall power conversion efficiency over 14 %.